2018
DOI: 10.1371/journal.pone.0205108
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Ccbe1 affects cardiac-specification and cardiomyocyte differentiation in mouse embryonic stem cells

Abstract: Understanding the molecular pathways regulating cardiogenesis is crucial for the early diagnosis of heart diseases and improvement of cardiovascular disease. During normal mammalian cardiac development, collagen and calcium-binding EGF domain-1 (Ccbe1) is expressed in the first and second heart field progenitors as well as in the proepicardium, but its role in early cardiac commitment remains unknown. Here we demonstrate that during mouse embryonic stem cell (ESC) differentiation Ccbe1 is upregulated upon emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In agreement with a possible role during cardiogenesis in mice, disruption of normal CCBE1 activity by shRNA knockdown (KD) or by a blocking antibody in differentiating mouse embryonic stem cells (mESCs) in vitro, results in a strong decrease in the expression of several cardiac lineage markers without affecting the pan-mesoderm marker BRACHYURY (Bover et al, 2018). Moreover, this in vitro model for cardiac differentiation demonstrated that, as occurs during mouse and chick cardiac development, high Ccbe1 expression correlates with the onset of cardiac specification, as observed in SHF and PE cardiac progenitors (Facucho-Oliveira et al, 2011;Furtado et al, 2014;Bover et al, 2018). In addition, Ccbe1 KD resulted in an impairment of embryoid body (EB) growth caused by reduced cell proliferation and a relative increase in cell death, especially from day 4 onwards (Bover et al, 2018).…”
Section: Expression and Function During Early Heart Developmentmentioning
confidence: 69%
See 3 more Smart Citations
“…In agreement with a possible role during cardiogenesis in mice, disruption of normal CCBE1 activity by shRNA knockdown (KD) or by a blocking antibody in differentiating mouse embryonic stem cells (mESCs) in vitro, results in a strong decrease in the expression of several cardiac lineage markers without affecting the pan-mesoderm marker BRACHYURY (Bover et al, 2018). Moreover, this in vitro model for cardiac differentiation demonstrated that, as occurs during mouse and chick cardiac development, high Ccbe1 expression correlates with the onset of cardiac specification, as observed in SHF and PE cardiac progenitors (Facucho-Oliveira et al, 2011;Furtado et al, 2014;Bover et al, 2018). In addition, Ccbe1 KD resulted in an impairment of embryoid body (EB) growth caused by reduced cell proliferation and a relative increase in cell death, especially from day 4 onwards (Bover et al, 2018).…”
Section: Expression and Function During Early Heart Developmentmentioning
confidence: 69%
“…Moreover, this in vitro model for cardiac differentiation demonstrated that, as occurs during mouse and chick cardiac development, high Ccbe1 expression correlates with the onset of cardiac specification, as observed in SHF and PE cardiac progenitors (Facucho-Oliveira et al, 2011;Furtado et al, 2014;Bover et al, 2018). In addition, Ccbe1 KD resulted in an impairment of embryoid body (EB) growth caused by reduced cell proliferation and a relative increase in cell death, especially from day 4 onwards (Bover et al, 2018). This cardiac fate during mESCs differentiation is EB size, growth factor signaling and ECM proteins niche dependent, but in particular, how mESCs interact with this developmental niche (Czyz and Wobus, 2001;Bratt-leal et al, 2009;Goh et al, 2013;Higuchi et al, 2013;Taylor-Weiner et al, 2013;Zeng et al, 2013).…”
Section: Expression and Function During Early Heart Developmentmentioning
confidence: 71%
See 2 more Smart Citations
“…Undifferentiated Dand5 KO and the respective E14 WT control mESC lines were used to test cells pluripotency potential and spontaneous differentiation by the hanging droplet method (Bover et al, 2018). Briefly, cells were dissociated into a single cell suspension and resuspended in fresh mESC medium without LIF.…”
Section: Mescs Differentiation Through Embryoid Bodies Formationmentioning
confidence: 99%